Kontroversen um die lexikographische Theorie - Monika Bielińska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Discussions on the status and nature of lexicography have been ongoing since at least the 1960s. Some of the most frequently discussed issues concern lexicographical theory, including its very existence, which some scholars find problematic. And if it is considered to exist, questions as to what can be treated as a lexicographic theory arise: Is it a theory of dictionary making practice? Is it a linguistic theory? Is it a separate lexicographical theory? The aim of the article is to present and comment on the divergent positions. Finally, the author draws attention to the factors that cause that the discussion on lexicographical theory is not always conducted at the appropriate scientific level.